The Implementation of the Humanistic Learning Model in the Learning of Islamic Religious Education in Junior High School - Afandi, Rahman; Ningsih, Putri Nofiana (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The objective of this study is to analyze the patterns of application of the humanistic learning model, specifically within the context of teaching Islamic Religious Education (PAI). The research was conducted at Walisongo Kembaran Islamic Junior High School and falls under the category of field research. In this research, the data encompasses the application of the humanism learning model in the context of Islamic Religious Education (PAI) at Walisongo Kembaran Islamic Junior High School. The sources of data for this study originate from both the teachers and students associated with Walisongo Kembaran Islamic Junior High School. The data collection technique employed in this research involves observation, interviews, and documentation. Meanwhile, the data analysis technique utilizes a descriptive-qualitative approach through three steps: data reduction, data presentation, and drawing conclusions. As a result, the implementation of the humanistic learning model in Islamic Religious Education (PAI) at Walisongo Kembaran Islamic Junior High School, using methods such as lectures, question and answer sessions, problem-solving, and discussions, has been aligned with and produced values in educational humanism. These values include the creation of an enjoyable learning atmosphere, the principle of developing students' potential, the principle of respecting opinions, fostering creativity, establishing connections with real-life situations, and acknowledging the freedom to make efforts. The learning model is based on the principles of fulfilling the desire to learn, meaningful learning, learning without punishment, and learning and change.